Analysis of Environmental-Friendly Aspects of Floating Nets in Batu Putih Atas Village, Bitung City Based on Responsible Fisheries Principles - Elsari Tanjung Putri; Katili, Lidya; Heru Santoso; Manengkey, Jenny I.; Saeful A. Tauladani; Franky Adrian Darondo; Karyanto (Zona Laut : Jurnal Inovasi Sains Dan Teknologi Kelautan, 2025)
To conserve fish resources, especially pelagic species, it is necessary to use environmentally friendly fishing gear according to the principles of responsible fisheries management. Bagan is a fishing gear that catches small pelagic fish as the primary target fish and is commonly found in Batu Putih Atas Village, Bitung City. This study analyzes the environmentally friendly aspects of Bagan, operated by local fishermen, based on CCRF principles. The research was conducted using a survey method using a questionnaire containing nine criteria with a weighted score of 1-4 for each criterion. Data analysis used descriptive quantitative. The results show that the type of Bagan used is floating Bagan, considered very environmentally friendly, with a weighted score of 30.2. This gear has a reasonably low selectivity but does not damage the habitat, is safe for fishers and consumers, and has minimal impact on biodiversity, low bycatch, and no protected fish. It is also socially acceptable and profitable for fishers.